Human colon cancer HT-29 cell death responses to doxorubicin and Morus Alba leaves flavonoid extract - Fallah, S; Karimi, A; Panahi, G; Gerayesh Nejad, S; Fadaei, R; Seifi, M (Cellular and Molecular Biology, 2016)
The mechanistic basis for the biological properties of Morus alba flavonoid extract (MFE) and chemotherapy drug of doxorubicin on human colon cancer HT-29 cell line death are unknown. The effect of doxorubicin and flavonoid extract on colon cancer HT-29 cell line death and identification of APC gene expression and PARP concentration of HT-29 cell line were investigated. The results showed that flavonoid extract and doxorubicin induce a dose dependent cell death in HT-29 cell line. MFE and doxorubicin exert a cytotoxic effect on human colon cancer HT-29 cell line by probably promoting or induction of apoptosis.